PERISTIWA FITNAH KUBRO: SEJARAH DAKWAH YANG HARUS DILURUSKAN - Rahmat Hidayat; Daud Rasyid; Riska Ramdani; Rambang Basari; Retna Dwi Estuningtyas (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2025)
The Fitnah al-Kubra is one of the most tragic events in Islamic history and is the primary cause of sectarian divisions among Muslims. The term